Implikasi Hukum Pasca Penetapan Pengadilan Nomor 624/Pdt.P/2021/PN Dps tentang Perubahan Identitas Gender terhadap Kepastian Hukum Pemohon Penggantian Jenis Kelamin: Studi Perbandingan Kompilasi Hukum Islam, Hukum Perdata dan Hukum Adat di Indonesia - Rizka Hanum Mendrofa; Rosnidar Sembiring; Utary Maharany Barus (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes the legal construction and juridical implications of gender identity changes in Indonesia following Court Determination Number 624/Pdt.P/2021/PN.Dps, focusing on medical classification as well as its consequences within civil law, Islamic law and customary law, while also assessing legal certainty. The method employed is normative juridical research supported by empirical data through interviews with the Indonesian Ulema Council (MUI), plastic surgeons and clinical psychologists. The findings indicate a clear distinction between corrective procedures for Disorders of Sex Development (DSD) and psychosocial-based gender transition. Court determinations provide administrative legitimacy but remain unaligned with substantive law, thus requiring the integration of biological validation and psychological assessment in judicial reasoning.